Corrigendum to “Wetting state and mechanical property alteration for the Fe3Si films using rapid thermal annealing under various temperatures” [Heliyon Volume 9, Issue 12, December 2023, Article e22511] - Nattakorn Borwornpornmetee; Thawichai Traiprom; Takafumi Kusaba; Phongsaphak Sittimart; Hiroshi Naragino; Boonchoat Paosawatyanyong; Tsuyoshi Yoshitake; Nathaporn Promros (Heliyon, 2025)
[This corrects the article DOI: 10.1016/j.heliyon.2023.e22511.].
Keywords: Aluminum Alloy Microstructure Properties; Aluminum Alloys Composites Properties; Microstructure and mechanical properties